Soluble factors released by peripheral blood-derived CAR-NK cells cause bystander myeloid cell activation - Khanal, Supreet; Baer, Alan; Hossain, Md Kamal; Colon-Moran, Winston; Panthi, Santosh; Bhattarai, Nirjal (Frontiers in Immunology, 2024)
IntroductionCAR-T cell therapy is associated with life-threatening inflammatory toxicities, partly due to the activation and secretion of inflammatory cytokines by bystander myeloid cells (BMCs). However, due to limited clinical data, it is unclear whether CAR-NK cells cause similar toxicities.MethodsWe characterized the soluble factors (SFs) released by activated human CAR-T and CAR-NK cells and assessed their role in BMC activation (BMCA).ResultsWe found that SFs from both activated, peripheral blood-derived CAR-T (PB-CAR-T) and CAR-NK (PB-CAR-NK) cells induced BMCA; however, PB-CAR-NK cells caused significantly lower BMCA compared to PB-CAR-T cells. Interestingly, SFs from cord-blood-derived (CB) NK cells caused little to no BMCA, consistent with previous clinical studies showing minimal inflammatory toxicity with CB-CAR-NK cells. Comparative analysis of SFs released by PB-NK and PB-CAR-NK cells following CAR-dependent and CAR-independent activation revealed several candidate factors with the potential to cause BMCA. Antibody-mediated neutralization studies identified a combination of four factors that contribute to PB-CAR-NK cell-mediated BMCA. siRNA-mediated knockdown studies confirmed that inactivating these four factors in PB-CAR-NK cells significantly reduces BMCA. Importantly, neutralization or knockdown of these four factors did not affect CAR-NK cell potency.DiscussionThese data suggest that specific SFs released by PB-CAR-NK cells activate BMCs and have the potential to contribute to inflammatory toxicities. Furthermore, inactivation of these four factors in PB-CAR-NK cells could reduce inflammatory toxicities and improve safety of PB-CAR-NK cell therapy without compromising potency.